Analisis Penerapan Akuntansi Dana Sosial Pada Musyawarah Desa Pertanggungjawaban (MDPT) di BUMDESa Lancang Kuning Desa Rumbai Jaya - Nur Aisiyah Mulyati (Transformasi Manageria: Journal of Islamic Education Management, 2023)
The purpose of this study was to analyze the application of social fund accounting at the accountability village meeting (MDPT) in the BUMDes of Lancang Kuning, Rumbai Jaya Village. The technique is carried out using descriptive qualitative data obtained by case studies obtained by researchers. In general, the accounting applied by BUMDes is very good, for statements of financial position, activity reports, cash flow reports, and notes on financial statements in PSAK 45, there is already a separator in BUMDes. Keywords: PSAK 45, Social Funds, BUMDes.